PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT PADA MAHASISWA SEKOLAH DASAR DI KECAMATAN GALESONG UTARA KABUPATEN TAKALAR - A. Ulfiana Fitri; Andi Atssam Mappanyukki; Dian Anggraeni Rachman; Meliana Handayani; Nurl Fajriah Istiqamah; Andi Nurzakiah Amin; Sri Rezkiani Kas; Nur Inayah Ismaniar (Program Studi Ilmu Keolahragaan, 2022)
As an educational institution, schools have a strategic role and position in health promotion efforts. Children are an age group that is vulnerable to experiencing health problems because most of their time is spent outside the home environment and outside the supervision of their parents. When children are in the school environment, they can experience disease transmission from peers, from the school environment or they may consume food that does not meet health requirements. Children are also an age group that is easy to impart knowledge about personal hygiene to shape healthy behavior. This activity is carried out through socialization activities for students, especially to increase awareness of the importance of Clean and Healthy Behavior in the surrounding environment. This activity was carried out at UPT SDN No. 96 Kalongkong on the day of North Galesong District, Takalar Regency which was held on Thursday, June 23 2022 using a pre-post test. The results of the post test showed an increase in knowledge of UPT SDN No.96 Kalongkong students